The state of the reproductive system of adolescent girls after vaccination against human papillomavirus using a quadrivalent vaccine - Irina V. Karachentsova; Elena V. Sibirskaya; Mariya M. Fomina; Tatyana G. Dyadik (Педиатрическая фармакология, 2024)
Background. Currently, oncological diseases and their possible prevention are being actively studied. Cancer mortality remains high. A national project “Healthcare” has been started in Russia, including the Federal projects “Fighting Cancer” and “Development of Children’s Health Care, including the creation of a modern infrastructure for providing medical care to children”. In a number of regions, girls can be vaccinated against the human papillomavirus (HPV). The main reason for refusing HPV vaccination is an unfounded fear of negatively affecting the fertility and other bad data. The aim of the study is an investigation of the reproductive system of adolescent girls with completed course of vaccination against HPV using quadrivalent vaccine. Methods. We selected 65 schoolgirls in Moscow by analyzing medical documentation data. All of them were vaccinated against HPV and examined by a gynecologist. The state of their reproductive system was assessed. Results. Most girls received the vaccine at the age of 12–13, according to the regional vaccination calendar of the city of Moscow. They were vaccinated with the quadrivalent vaccine twice with an interval of 6 months; no adverse event was noted. The mean period of time since vaccination was 2.7 ± 1.1 years. The mean age of menarche, mean menstrual cycle length, and mean bleeding time were normal in girls vaccinated against HPV. Among menstrual disorders, dysmenorrhea and oligomenorrhea were most often observed, but the data did not differ from the population average. The incidence of abnormal uterine bleeding and breast pathology was lower. No papillomas were detected. Pubertal development corresponded to age of all girls. Conclusion. It has been established that vaccination against the human papillomavirus does not have a negative impact on the reproductive system of teenage girls. However, additional dynamic studies are needed at different age periods of girls and women vaccinated against HPV to confirm the positive effect on the sexual sphere and formation of strong adherence to vaccination.